Observaciones experimentales sobre el xenodiagnóstico en tripanosomiasis americana - Arrojo, Lyly (2001)
Seven third stage nymphs of Triatoma infestans were infected with Trypanosoma cruzi of mice during the acute phase. After a time of being positives, the triatomids became a microscopical negative in feces examination. The feces of these negative triatomids were inoculated to eight mice and controled from 16 to 44 days. Three mice (37,5%) showed infection of the blood. These results suggest the necessity to induce an infection in a mouse upon which, from the fifteenth day on, tests should be conducted in order to check for trypomastigotes.